Habitat preference and flowering‐time variation contribute to reproductive isolation between diploid and autotetraploid Anacamptis pyramidalis. (27th July 2016) - Pegoraro, L.; Cafasso, D.; Rinaldi, R.; Cozzolino, S.; Scopece, G.
Abstract: Tetraploid lineages are typically reproductively isolated from their diploid ancestors by post‐zygotic isolation via triploid sterility. Nevertheless, polyploids often also exhibit ecological divergence that could contribute to reproductive isolation from diploid ancestors. In this study, we disentangled the contribution of different forms of reproductive isolation between sympatric diploid and autotetraploid individuals of the food‐deceptive orchid Anacamptis pyramidalis by quantifying the strength of seven reproductive barriers: three prepollination, one post‐pollination prezygotic and three post‐zygotic. The overall reproductive isolation between the two cytotypes was found very high, with a preponderant contribution of two prepollination barriers, that is phenological and microhabitat differences. Although the contribution of post‐zygotic isolation (triploid sterility) is confirmed in our study, these results highlight that prepollination isolation, not necessarily involving pollinator preference, can represent a strong component of reproductive isolation between different cytotypes. Thus, in the context of polyploidy as quantum speciation, that generates reproductive isolation via triploid sterility, ecological divergence can strengthen the reproductive isolation between cytotypes, reducing the waste of gametes in low fitness interploidy crosses and thus favouring the initial establishment of the polyploid lineage. Under this light, speciation by polyploidy involves ecological processes and should not be strictly considered as a nonecological form of speciation.